Analisis Pemilihan Portofolio Optimal pada Kombinasi Indeks Bisnis-27 Menggunakan Single Index Model - Rina Fariana; Bayu Adi (Jurnal Studi Manajemen dan Bisnis, 2018)
Investment is an important thing for everyone as an alternative in the storage of funds and to gain profit. Investors are faced with two things in making investments, namely risk and return. Diversification is one way to minimize risk by forming a portfolio of stocks. This study aims to determine and analyze optimal portfolio selection using single index model.The type of research used in this research is descriptive research with quantitative approach. The object of this research is using the company collected in BISNIS-27 index, with the research period from 2011 to 2015. The data collection method used is purposive sampling, where the company to be analyzed is only companies listed in BISNIS-27 stock index consistently during nine (9) periods from February 1, 2011 to July 31, 2015, and stocks are not suspended during the period February 1, 2011 to July 31, 2015. Data required in the analysis of data is historical price of stocks and IHSG (Indeks Harga Saham Gabungan). Analyzer using microsoft excel.